The Relationship between Maternal Parenting and Stunted Toddlers Aged 24-59 Months in Sepakek Village, Pringgarata District - Hudari, Ahmad; Halimatunnisa, Maulin; Mastuty, Amalia (Balai Publikasi Indonesia, 2025)
Stunting is a condition of failure to grow in children resulting from chronic malnutrition so that the child is too short for his age. According to research data from the World Health Organization (WHO) in 2020, the prevalence of stunting in Indonesia reached 31.8% of cases, and in NTB the prevalence of stunting reached 32.7% in 2022, this figure is still categorized as a health problem in Indonesia because WHO has set a minimum figure. stunting in a country is below 20%. The aim of this research was to determine the relationship between maternal parenting patterns and stunting toddlers aged 24-59 months in Sepakek Village, Pringgarata District. This research design is analytical correlative with a cross sectional approach. With a sample of 54 respondents taken using purposive sampling technique. The research instruments were questionnaires and microtoises. Analysis of this research data used the chi-square test. The results showed that 79.6% of mothers' behavior was in the good category, while 20.4% of mothers' behavior was in the less good category with the results of the chi-square test (p-value 0.189>0.05). The conclusion is that the results show that there is no significant relationship between maternal parenting patterns and stunting toddlers aged 24-59 months in Sepakek Village, Pringgarata District. Mother's parenting advice is not a factor in the occurrence of stunting however, mother's parenting practices must be considered together because good parenting will have an impact on toddlers and vice versa